TEACHER PROFICIENCY IN ENGLISH LANGUAGE TEACHING: A COMPREHENSIVE ANALYSIS - Ishankhudjaeva Feruza Abduboriyevna (International Journal of Literature and Language Studies, 2026)
Abstract; Teacher proficiency is a fundamental determinant of success in English Language Teaching (ELT), particularly in contexts where English is taught as a foreign language. Despite global expansion of English education, many systems continue to face persistent challenges related to teachers’ linguistic competence, communicative ability, and pedagogical effectiveness. These challenges significantly affect classroom interaction and student learning outcomes. Findings indicate that teacher proficiency is shaped by systemic, institutional, and individual factors, including exam-oriented education, limited communicative exposure and insufficient professional development. This article is discussed that sustainable improvement requires reform in teacher education, increased communicative practice, and integration of modern educational technologies.